Publicity of Sido Muncul Corporate Social Responsibility News Content During Covid-19 Pandemic - Steven Leo Naryi Lukman; Rustono Farady Marta; Sugeng Wahjudi (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2020)
The COVID-19 pandemic which took place in Indonesia in 2020 was an adverse event for various sectors in the country. This case attracted a high level of public attention. Various companies engaged in carrying out corporate social responsibility activities in helping areas affected by COVID-19, one of which was PT. Sido Muncul. CSR activities help companies to get a positive image and maintain customer loyalty through publicity on the online news portal. The purpose of this research is to describe the contents of the news on the online news portal about corporate social responsibility carried out by PT. Sido Muncul during the COVID-19 pandemic. The results of this paper, will describe in detail the types of news issued to report on CSR carried out by it. the researcher choose to analyze with content analysis method by Wimmer and Dominick, this method including; describe the contents of communication, to know about the characteristics of the message, and to supports the study of the effects of mass media. In gathering information and data, the study used qualitative approach with content analysis methods for 8 news items released by various online news portals during the COVID-19 pandemic, starting from March 2, 2020